2007
DOI: 10.1051/0004-6361:20066460
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén wave dissipation and topological properties of 3D coronal force-free magnetic fields

Abstract: We study the propagation and dissipation of Alfvénic perturbation in a 3D equilibrium structure within a WKB model. We assume small amplitude and small wavelength of the perturbation. The generation of small scales in the perturbation is related to the property that nearby magnetic lines move apart from each other locally. This property is quantified by means of the Kolmogorov entropy H of magnetic lines. We numerically calculate the distribution of H for a 3D complex force-free equilibrium, which models the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Since Alfvénic perturbations propagate along magnetic lines, at separatrices the perturbation pattern is strongly stretched. Malara et al (2007) have shown that the rate of small-scale generation is particularly high at such locations. We will show that smallscale structures in the perturbation are located at separatrices.…”
Section: Equilibrium Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Since Alfvénic perturbations propagate along magnetic lines, at separatrices the perturbation pattern is strongly stretched. Malara et al (2007) have shown that the rate of small-scale generation is particularly high at such locations. We will show that smallscale structures in the perturbation are located at separatrices.…”
Section: Equilibrium Structurementioning
confidence: 99%
“…A more complex topology of magnetic field lines corresponds to a more efficient generation of small scales (Malara et al 2007). In particular, Malara et al (2005) consider a complex magnetic configuration that represents a model for the coronal field above a quiet-Sun region.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that the creation of a dissipative scale can be made exponentially fast (dk/dt ∝ const.·k), with the associated time scale being proportional to ln S S 1/3 S (Similon & Sudan 1989;Petkaki et al 1998;Malara et al 2007). The latter improved efficiency of the dissipation results by essentially considering a more complex magnetic geometry, with the property of local exponential separation or divergence of neighboring magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the diffusive length scale is proportional to S −1/2 . Therefore, fast dissipation is possible in three-dimensional chaotic magnetic fields (Similon & Sudan 1989;Petkaki et al 1998;Malara et al 2000Malara et al , 2007 and in twodimensional regular ones (Smith et al 2007;Malara et al 2003;Ruderman et al 1998), provided they possess a degree of complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation